2023
DOI: 10.1088/2058-6272/aca372
|View full text |Cite
|
Sign up to set email alerts
|

Screening effect of plasma flow on the resonant magnetic perturbation penetration in tokamaks based on two-fluid model

Abstract: Numerical simulation on the resonant magnetic perturbation penetration is carried out by the newly-updated initial value code MDC (MHD@Dalian Code). Based on a set of two-fluid four-field equations, the bootstrap current, parallel, and perpendicular transport effects are included appropriately. Taking into account the bootstrap current, a mode penetration-like phenomenon is found, which is essentially different from the classical tearing mode model. To reveal the influence of the plasma flow on the mode penetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 54 publications
(55 reference statements)
0
3
0
Order By: Relevance
“…( 2) and the magnetic island width. [45] Figure 2(b) gives the dependence of average saturated magnetic island width on δ . In this context, "average" refers to the mean value of the magnetic island width during the saturation phase, considering the periodic oscillations observed in the magnetic island width.…”
Section: Numerical Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…( 2) and the magnetic island width. [45] Figure 2(b) gives the dependence of average saturated magnetic island width on δ . In this context, "average" refers to the mean value of the magnetic island width during the saturation phase, considering the periodic oscillations observed in the magnetic island width.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…For instance, the simulation results are adopted to explain experimental observations in ASDEX-U [34] and DIII-D. [56] In simulations related to two-fluid dynamics, cylindrical geometry has also been extensively employed. [42,44,45,57] Simulation results have demonstrated the ability to elucidate certain phenomena observed in experiments. Paz-Soldan et al found alignment between simulation results by TM1 code, a nonlinear two-fluid MHD model with cylindrical geometry, and experimental island healing.…”
Section: Model Equationsmentioning
confidence: 99%
See 1 more Smart Citation